A Model of the IMF as a Coinsurance Arrangement - Ralph Chami; Sunil Sharma; Ilhyock Shim (Kiel Institute for the World Economy (IfW), 2007)
The paper shows that an IMF-like coinsurance arrangement among countries can play a useful role in the global financial system. The operation of the coinsurance arrangement is examined under different loan contracts. It shows that, if the IMFs objective is to safeguard its resources and be concerned about the welfare of the borrower, an ex ante loan contract is more likely to create the right incentives than an ex post loan contract. Such contracts highlight the need for precommitment to contend with the Samaritans dilemma and time inconsistency, and state-contingent repayment schemes to deal with King Lears dilemma.
Keywords: G22; F02; D82; F33; 330; IMF; coinsurance arrangement; moral hazard; Samaritans dilemma; King Lears dilemma